Suitability of maize (Zea mays) based inteteropping system - PATRA, B C; MANDAL, B B; MANDAL, B K; PADHI, A K (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during the summer 1993 and 1994 to study the performance of maize (Zea maysL.) + greengram (Phaseolus radiatus L.), blackgram (Phaseolus mungo L.), soybean [Glycine max (L.) Merr.], groundnut(Arachis hypogaea L.) and sesamc (Sesamum indicurn L.) intercropping for yield. Legumes at 1:1 row ratio not onlyimproved the yield components and grain yield of maize but also gave bonus yield, which increased the maize equivalentyield and combined yield with higher monetary advantage and biological efficiency / unit area and time over theirrespective monocultures. Sesame appeared to be more competitive and non-compatible with maize. However, maize +grecngram at 1:1 row ratio was found to be the most economically viable system with highest land equivalent ratio (1.54),monetary advantage ( Rs 5 973/ha), net return ( Rs 8 541 ) and net production value ( 1.83).